Development and Reform of Fishery Subsidies Under the Construction of Ecological Civilization - LI Jinyu; TIAN Tao; LIU Xinshan; YIN Zengqiang; WU Zhongxin; LI Qingxia (Haiyang Kaifa yu guanli)
Marine fishery plays a vital role in China’s economic system, and the issue of fishery subsidy policy has always been a research hotspot. In the face of the contradiction between the depletion of inland and offshore fishery resources and the growing demand for aquatic products, the contradiction between the growth of fishing output and the continuous deterioration of the marine environment, how to use fishery subsidy policies to support the sustainable and healthy development of marine fisheries has aroused widespread concern in academia and the industry. From the perspective of ecological civilization construction, this paper discusses the development and transformation process of the fishery subsidy policy and its impact on the marine environment, analyzes the problems existing in the implementation of the current fishery subsidy policy, and gives corresponding suggestions from the aspects of structural design, legal development, and optimization of regulatory mechanism. Combined with foreign experience, it is believed that the construction of ecological civilization will guide future fishery subsidy policy of China in the future; we will vigorously promote the sustainable development of marine fisheries.